Prediction of 3-D nano-mesh flows by a micro-flow LBM and its evaluation against MD simulations. (29th June 2011) - Suga, K.; Takenaka, S.; Kinjo, T.; Hyodo, S.
In this paper, a Lattice Boltzmann Method (LBM) is evaluated for three-dimensional (3-D) continuum to non-continuum transitional flow regimes, and its performance for flows in a nano-porous medium is discussed. The equations used in the LBM are modified Lattice Boltzmann Equations (LBEs) introducing the diffuse-scattering wall boundary condition and a Knudsen number dependent relaxation-time along with the regularisation procedure. The evaluation is carried out by comparing the results with those of the Molecular Dynamics (MD) simulation. The results of the flows at Knudsen numbers Kn = 0.1 and 0.2 show good agreement in both simulations and confirm the reliability of the LBM.